Is It Feasible and Desirable to Collect Voluntarily Quality and Outcome Data Nationally in Palliative Oncology Care? - Currow, D.; Eagar, K.; Aoun, Samar; Fildes , D.; Yates, P.; Kristjanson, Linda (American Society of Clinical Oncology, 2008)
Hospice/palliative care is a critical component of cancer care. In Australia, more than 85% ofpeople referred to specialized hospice/palliative care services (SHPCS) have a primary diagnosis ofcancer, and 60% of people who die from cancer will be referred to SHPCS. The Palliative CareOutcomes Collaboration (PCOC) is an Australian initiative that allows SHPCS to collect nationallyagreed-upon measures to better understand quality, safety, and outcomes of care. This articledescribes data (October 2006 through September 2007) from the first 22 SHPCS, with more than100 inpatient admissions annually. Data include phase of illness, place of discharge, and, at eachtransition in place of care, the person?s functional status, dependency, and symptom scores. Dataare available for 5,395 people for 6,379 admissions. After categorizing by phase of illness anddependency, there remain at the end of each admission 12-fold differences (mean, 26%; range,4% to 52%) in the percentage of patients who became stable after an unstable phase; seven-folddifferences (mean, 22%; range, 6% to 41%) in the percentage of patients with improvedsymptom scores, five-fold differences (mean, 25%; range, 12% to 64%) in discharge back to thecommunity, four-fold differences (mean, 10%; range, 4% to 16%) in improved function, andthree-fold differences in the length of stay (mean, 14 days; range, 6 to 19 days). PCOC shows itis feasible to collect quality national palliative care outcome data voluntarily. Variations in outcomesjustify continued enrollment of services. Benchmarking should include all patients whose cancerwill cause death and explore observed variations.